Global Transcriptional Analysis of Burkholderia Pseudomallei High and Low Biofilm Producers Reveals Insights into Biofilm Production and Virulence - Chin, Chui Yoke; Hara, Yuka; Ghazali, Ahmad Kamal; Yap, Soon Joo; Kong, Cin; Wong, Yee Chin; Rozali, Naufal; Koh, Seng Fook; Hoh, Chee Choong; Puthucheary, Savithri D.; Nathan, Sheila (BioMed Central, 2015)
Background Chronic bacterial infections occur as a result of the infecting pathogen’s ability to live within a biofilm, hence escaping the detrimental effects of antibiotics and the immune defense system. Burkholderia pseudomallei, a gram-negative facultative pathogen, is distinctive in its ability to survive within phagocytic and non-phagocytic cells, to persist in vivo for many years and subsequently leading to relapse as well as the development of chronic disease. The capacity to persist has been attributed to the pathogen’s ability to form biofilm. However, the underlying biology of B. pseudomallei biofilm development remains unresolved. Results We utilised RNA-Sequencing to identify genes that contribute to B. pseudomallei biofilm phenotype. Transcriptome analysis of a high and low biofilm producer identified 563 differentially regulated genes, implying that expression of ~9.5 % of the total B. pseudomallei gene content was altered during biofilm formation. Genes involved in surface-associated motility, surface composition and cell wall biogenesis were over-expressed and probably play a role in the initial attachment of biofilms. Up-regulation of genes related to two component signal transduction systems and a denitrification enzyme pathway suggest that the B. pseudomallei high biofilm producer is able to sense the surrounding environmental conditions and regulate the production of extracellular polymeric substance matrix, a hallmark of microbial biofilm formation. Conclusions The transcriptome profile described here provides the first comprehensive view of genes that contribute to the biofilm phenotype in B. pseudomallei.